The PESTEL Dynamic of Pandemics: The Theory of Manufactured Crisis, the Commercial, Economic Enterprise of Plagues, Pestilences and Pathogens - Ferguson, Gerline (Digital Repository of Theses - SSBM Geneva, 2025)
The purpose and intent of this academic thesis research paper is to fill in the knowledge gap of current academic literature. To add to the existing repository of scholastic knowledge. It seeks to take an in-depth look at pandemics wholistically by thoroughly examining the current empirical evidential data on disease outbreak on economies globally and throughout history. This paper will assess pandemics through the theories of economic crisis. It will also evaluate the Political, Economic, Social, Technological, Environment and Legal forces using the “PESTEL” framework, crisis management concepts, and strategic management on disease control and outbreaks. It will observe pandemics through the microscopic and macroscopic lenses of business, investments, global trade, commerce, economics and finance, using business models, methods, systems, cycles, tools, strategies and frameworks. This academic paper seeks to analyze the scientific notion, and the spillover effects of pandemics throughout history juxtapose to the present era, whereby mapping out possible predictive future patterns, and probable trajectories, of both short-, mediumlong-term patterns. This research is a thorough multifaceted approach and it is an elaborately meticulous assessment to explore and dissect the vast impact of pandemics on society and global economies on all levels. This paper seeks to deeply analyze the evolutionary process both the physiological characteristics, the psychological, the sociological, the theoretical, the philosophical aspects from ancient pre-historic antiquity to this modern era and beyond. It offers a comprehensive evidentiary evaluation of pandemics and their widespread impacts on societal developments and global advancements.